1971
DOI: 10.2135/cropsci1971.0011183x001100050043x
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Resistance to Brown Planthoppers and Green Leafhoppers in Oryza sativa L.1

Abstract: The genetics of resistance of several rice cultivars (Oryza saliva L.) to the brown planthopper, Nilaparvata o lugens (Stal), and to the green leafhopper, Nephotettix impicticeps (Ishihara), was studied in the greenhouse. Two testing techniques were developed and employed. In one, 7-day-old seedlings were infested with insects and then classified on the basis of insect injury. In the other a known number of insects were caged on tillers of 6-weekold plants and insect survival was used as the criterion for clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
75
1

Year Published

1974
1974
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(79 citation statements)
references
References 0 publications
3
75
1
Order By: Relevance
“…'IR26', the first BPH-resistant cultivar developed by the International Rice Research Institute, carries the BPH resistance gene Bph1. The cultivar 'IR36' carries bph2 (Athwal et al, 1971). All these indicate that most resistant cultivars carry one type of resistance gene, against either WBPH or BPH.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…'IR26', the first BPH-resistant cultivar developed by the International Rice Research Institute, carries the BPH resistance gene Bph1. The cultivar 'IR36' carries bph2 (Athwal et al, 1971). All these indicate that most resistant cultivars carry one type of resistance gene, against either WBPH or BPH.…”
Section: Discussionmentioning
confidence: 95%
“…It has previously been shown that a single BPH-resistant gene can operate against different biotypes. The dominant gene Bph1 conferred resistance to biotypes 1 and 3 (Athwal et al, 1971). Two closely linked genes, Bph3 and bph4, conferred resistance to all the four biotypes .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar result was obtained with another recessive BPH resistance gene. The bph2 gene was first found in a cultivar ASD7 and behaved as a recessive gene in a cross of TN1/ASD7 (Athwal et al 1971). However, the studies on the resistance segregation in a large number of F 2 and F 3 progenies from crosses of ASD7/C418 and Tsukushibare/Norin-PL4, respectively confirmed the dominant nature of bph2 (Murai et al 2001, Murata et al 1998.…”
Section: Discussionmentioning
confidence: 99%
“…In the breeding of rice plants, several genes involved in resistance to hemipteran insects such as leafhoppers have been identified (Athal et al 1971;Lakshminarayama et al 1977;Siwi et al 1977;Sidhu et al 1979;Rezaul et al 1982;Ghani et al 1988;Kabir et al 1988). However, the rice genes involved in resistance to lepidopteran pests have not been identified.…”
mentioning
confidence: 99%